EV HEALTH: DEVELOPING ELECTRONIC TOOLS FOR BATTERY VOLTAGE FAULT DIAGNOSIS IN NEW ENERGY VEHICLES - Li , Hua Chen, Meng; Yue, Wang Xin (Research Journal of Engineering and Allied Sciences, 2024)
The rapid development of the new energy automobile industry promotes the reform of the concept and method of automobile maintenance. In the context of the extensive application of information technology, intelligent diagnosis technology has been effectively promoted due to its advantages of accurate detection and low cost. The use of electronic diagnostic technology to diagnose and maintain the battery voltage faults of new energy vehicles has various advantages, which can realize the accurate investigation of voltage faults and provide effective information reference for fault maintenance. Clarifying the fault position in a short time and judging the degree of fault harm can greatly improve the effectiveness of battery voltage fault handling of new energy vehicles. This work mainly discusses the establishment of the battery voltage fault diagnosis mechanism of new energy vehicles using electronic diagnosis technology. Based on electronic diagnosis technology, this work clarified the specific application in automobile battery voltage fault diagnosis to guide the improvement of the diagnostic mechanisms